Psychometric properties of the Portuguese Dutch Work Addiction Scale - Elisabete Borges; Carlos Sequeira; Teresa Martins; Cristina Queirós; Maria Pilar Mosteiro-Díaz (SciELO, 2021)
ABSTRACT Objective To analyse the psychometric properties of the Dutch Work Addiction Scale in a sample of Portuguese nurses. Method A methodological study was conducted with 1,030 Portuguese nurses. A sociodemographic/professional questionnaire and the Dutch Work Addiction Scale applied between October and December 2019. Results The Confirmatory Factorial Analyses confirmed the factorial structure of two dimensions, namely Working Excessively (α = .730) and Working Compulsively (α = .752), grounded on the theoretical model of workaholism; the reliability values were considered adequate. Nurses presented a moderate level of workaholism, with a higher mean value for Working Excessively. Conclusion The results raised the issue of workaholism and highlighted the need for further study. The Portuguese version of the DUWAS presented good psychometric characteristics and can be considered a valid and useful instrument to identify this problem.